2019
DOI: 10.1634/theoncologist.2019-0047
|View full text |Cite
|
Sign up to set email alerts
|

Degree of MDM2 Amplification Affects Clinical Outcomes in Dedifferentiated Liposarcoma

Abstract: Background Dedifferentiated liposarcomas (DDLPS) are mesenchymal tumors associated with universally poor response to treatment. Genomic amplification of murine double minute 2 (MDM2) is used as a diagnostic biomarker; however, no established biomarkers exist to guide DDLPS treatment. In the largest study of its kind, we report that the extent of MDM2 amplification, not simply the presence of MDM2 amplification, may be biologically important to the actions of DDLPS. Patients and Methods The distribution of MDM2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 20 publications
1
25
3
Order By: Relevance
“…15,16 High-amplification levels of MDM2 have been reported to correlate with poor outcomes in DDLPS. 17,18 In this study, although the MDM2 amplification level tended to be associated with poor OS, the correlation was not signifi- was reported to be associated with WDLPS histological type and F I G U R E 7 Association of distant metastasis-free survival (DMFS) with A, histological tumor grade, B, cellular atypia, C, MDM2 immunoreactivity, and D, HMGA2 immunoreactivity good prognosis in a study including both WDLPS and DDLPS cases. 7 However, another study showed that HMGA2 was significantly overexpressed in DDLPS samples compared with WDLPS samples from the same cases and that HMGA2 rearrangements occurred more frequently in DDLPS components.…”
Section: Pathological Findingscontrasting
confidence: 50%
“…15,16 High-amplification levels of MDM2 have been reported to correlate with poor outcomes in DDLPS. 17,18 In this study, although the MDM2 amplification level tended to be associated with poor OS, the correlation was not signifi- was reported to be associated with WDLPS histological type and F I G U R E 7 Association of distant metastasis-free survival (DMFS) with A, histological tumor grade, B, cellular atypia, C, MDM2 immunoreactivity, and D, HMGA2 immunoreactivity good prognosis in a study including both WDLPS and DDLPS cases. 7 However, another study showed that HMGA2 was significantly overexpressed in DDLPS samples compared with WDLPS samples from the same cases and that HMGA2 rearrangements occurred more frequently in DDLPS components.…”
Section: Pathological Findingscontrasting
confidence: 50%
“…Thus, an amplification in MDM2 results in a shift towards pro-growth pathways. Our previous work demonstrated that higher levels of MDM2 amplification are associated with worsened overall survival and resistance to DNA-damaging chemotherapy in liposarcomas [8,9]. Interestingly, although DDLPS are of fat origin, they produce scant fat themselves and resemble undifferentiated pleomorphic or spindle cell sarcoma, typically showing moderate or high cellularity, with moderate to marked pleomorphism [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the largest study of its kind Bill et al correlated the degree of MDM2 amplification with clinical and biological outcomes. Elevated MDM2, as measured by genomic amplification and mRNA expression was associated with a shortened time to recurrence [43]. Other studies have confirmed a higher MDM2 copy number is associated with poorer outcomes, poorer response to cytotoxic therapy and interestingly a higher propensity for a retroperitoneal location [44,45].…”
Section: Figmentioning
confidence: 84%